2007
DOI: 10.1194/jlr.m600505-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

On the singular, dual, and multiple positional specificity of manganese lipoxygenase and its G316A mutant

Abstract: manganese lipoxygenase (Mn-LO) oxygenates 18:3n-3 and 18:2n-6 to bis-allylic 11S-hydroperoxy fatty acids, which are converted to 13R-hydroperoxy fatty acids. Other unsaturated C 16 -C 22 fatty acids, except 17:3n-3, are poor substrates, possibly because of ineffective enzyme activation (Mn II YMn III ) by the produced hydroperoxides. Our aim was to determine whether unsaturated C 16 -C 22 fatty acids were oxidized by Mn III -LO. Mn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…1B. Analysis of the products during the rapid and almost linear increase in UV absorbance at 235 nm, which is attributable mainly to the formation of 15R-hydroperoxy-5Z,8Z,11Z,13E-eicosatetraenoic acid (15-HPETE) (26), showed that 13-hydroperoxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (13-HPETE) accounted for ?10-14% of the products during the upper part of the linear phase. This number was below 1% already at the peak of UV absorbance and was ,0.1% at later time points (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B. Analysis of the products during the rapid and almost linear increase in UV absorbance at 235 nm, which is attributable mainly to the formation of 15R-hydroperoxy-5Z,8Z,11Z,13E-eicosatetraenoic acid (15-HPETE) (26), showed that 13-hydroperoxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (13-HPETE) accounted for ?10-14% of the products during the upper part of the linear phase. This number was below 1% already at the peak of UV absorbance and was ,0.1% at later time points (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…20:4n-6 is a poor substrate of Mn-LOX and required large amounts of enzyme for rapid transformation (25,26). Oxidation of 20:4n-6 by Mn-LOX and analysis of the products are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effluents from the column were combined with isopropyl alcohol/water (3/2) in a ratio of ~2:1 from a second HPLC pump (21) and then introduced by electrospray into a linear ion trap mass spectrometer (LTQ, Thermo) with analysis of carboxylate anions. The ion isolation width was set at 5 for anions of HPOME (m/z 313→ full scan) in the first selection and 1.5 at the final selection of MS 3 analysis of HPOME (m/z 313 → 295 → full scan).…”
Section: Analytical Cp-hplc Separations With In-line Lc-ms Analysismentioning
confidence: 99%